Conceptual Implementation of Islamic Religious Education: Patterns And Methods of Early Children’s Education In The Family Environment - Hafid; Admizal, Iril; Mandala, Ican (Institut Agama Islam Negeri Kerinci, 2023)
Education is an essential aspect for an individual, especially for a child. Islamic religious education, particularly during early childhood, is a specific and urgent concern addressed by the family environment. This is because in the current era of digitalization, parents are required to prepare their children to adapt and face the developments of the time. Moral challenges that can impact a child necessitate the teaching of Islamic religious education from an early age. The effectiveness of this education is carried out through the family environment. The implementation of Islamic religious education undoubtedly requires a well-conceptualized educational pattern and effective methods to support the child's education. Therefore, this research aims to analyze the patterns or concepts and relevant methods used for the education of children in the family environment. This qualitative research utilizes a literature review method to analyze research sources. Data is collected from various books, journals, and articles relevant to the research focus. The data is then presented in descriptive form and analyzed based on the stages of data reduction, data display, and conclusion drawing. The results of this research reveal conceptual frameworks for implementing Islamic religious education in early childhood through various methods, including setting an example or role-modeling for children, using methods of rewarding or acknowledging their achievements, providing advice, instilling habits aligned with Islamic guidance, direct practice in daily life to familiarize children with doing good deeds, and communication methods involving dialogue with young children. The implementation of Islamic religious education using these methods will shape attitudes, behavior patterns, and morals capable of facing the challenges of the times.